Մանր եղջերավոր կենդանիների բրուցելոզի ախտորոշումը և համաճարակաբանական վերլուծությունը Հայաստանի Հանրապետության որոշ մարզերում - Սարգսյան, Մարիամ; Բալասանյան, Հրաչուհի; Թովմասյան, Գոհար; Գրիգորյան, Հովիկ (ՀԱԱՀ հիմնադրամ)
Бруцеллез мелкого рогатого скота (Br. melitensis) – зоонозное, хроническое, эндемическое инфекционное заболевание, крайне опасное для человека и овцеводческих хозяйств. Для выявления заражения овцеводческих хозяйств Арагацотнской, Гегаркуникской и Котайкской областей РА были применены различные эпидемиологические, клинические и серологические методы: тест Роз Бенгал, реакция агглютинации, а также иммуноферментный анализ (ELISA). Согласно данным эпизоотологического анализа, коэффициент заболеваемости бруцеллезом (бактерионосительство) составил 0.167 (16. 7 %), а экономический ущерб от вынужденного убоя – 1 625 000 драмов. Brucellosis of small cattle is a zoonotic, chronic, endemic, infectious disease that poses a serious threat to human health and the development of sheep farms. The causative agent of the disease belongs to the Brucellacaea family and the Brucella genus. Br. melitensis is a facultative intracellular pathogen, gram-negative, motile, aerobic, non-spore- and capsule-forming of various shapes (spherical, ovoid, spiny), 0.3-0.6 μm in size, a highly aggressive microorganism that enters the animal body through the alimentary tract, mucous membranes, genitourinary tract, damaged skin, and some- times through the respiratory tract. Then the pathogen affects and multiplies in the host's phagocytic cells, monocytes, and the mononuclear macrophage system (lymph nodes, kidneys, spleen, bone marrow). It leads to a decrease in the weight gain of sick animals, death of fetuses, reproductive dysfunction and forced slaughter of animals. In order to diagnose brucellosis, the Rose Bengal test, agglutination reaction (AR) and enzyme-linked immunosorbent assay (ELISA) methods were used. The results of the research indicate that in recent years, brucellosis of small cattle has been registered in some settlements of the Aragatsotn, Gegharkunik and Kotayk regions of the Republic of Armenia, which has caused significant economic damage to sheep farms in these regions. It was found out that a tense epizootological situation has developed in sheep farms of the above-mentioned regions due to this type of brucellosis. The incidence rate of animals (microbiosis) was 0.167 (16.7 %), and the economic damage from the slaughter of sick animals was 1.625 thousand drams. In order to avoid the risk of epizootic outbreaks of the disease, unfavorable areas, aborted fetuses, and amniotic fluid were treated with 2-3 % aqueous solution of bleach containing active chlorine.
Keywords: Անասնաբուժական բժշկագիտություն